Production of rhizomes and chemical characterization of arrowroot flour and starch under different agronomic management (Research, Society and Development, 2022)
Arrowroot is an unconventional vegetable that produces rhizomes with high starch content, gluten free and has a high market value, however technical information on the cultivation of the crop is scarce in the literature. The objective of this work was to evaluate the rhizome yield, yield and chemical characteristics of arrowroot flour and starch, ‘Common’ variety, as a function of different forms of cultivation. The experiment was carried out in a randomized block design, in a 2 x 2 x 2 factorial scheme (the seedlings produced by rhizomes between 30 - 59 and between 60 - 100 g being evaluated; organic and conventional fertilization; sources of A1 and A2 fertilization recommendations). The moisture content, ash, protein and amount of pure starch for flour and starch were evaluated, as well as ether extract for starch. The recommendations following A1 proved to be more effective both for the production of flour and arrowroot starch, resulting in higher levels of pure starch and lower contaminants contrary. The different sizes of propagules, type of recommendation and fertilization affect the quality of the arrowroot flour and starch.